2009
DOI: 10.1152/ajpheart.01266.2008
|View full text |Cite
|
Sign up to set email alerts
|

CBP and p300 are essential for renin cell identity and morphological integrity of the kidney

Abstract: The mechanisms that govern the identity of renin cells are not well understood. We and others have identified cAMP as an important pathway in the regulation of renin synthesis and release. Recently, experiments in cells from the renin lineage led us to propose that acquisition and maintenance of renin cell identity are mediated by cAMP and histone acetylation at the cAMP responsive element (CRE) of the renin gene. Ultimately, the transcriptional effects of cAMP depend on binding of the appropriate transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 35 publications
6
81
1
Order By: Relevance
“…Recently, in vitro and in vivo studies demonstrate the crucial role of the cAMP pathway on the acquisition and maintenance of the renin cell identity. 51,52 Activation of the cAMP pathway was proven to be of importance not only for the well known stimulation of renin release but also for vascular development early in fetal life. Conditional deletion of G␣ s in cells from the renin lineage such as arteriolar SMCs and mesangial cells results in almost complete absence of renin-expressing cells in the fetal kidney accompanied by blunted development of the preglomerular arterial tree.…”
Section: Role Of the Camp Pathwaymentioning
confidence: 99%
“…Recently, in vitro and in vivo studies demonstrate the crucial role of the cAMP pathway on the acquisition and maintenance of the renin cell identity. 51,52 Activation of the cAMP pathway was proven to be of importance not only for the well known stimulation of renin release but also for vascular development early in fetal life. Conditional deletion of G␣ s in cells from the renin lineage such as arteriolar SMCs and mesangial cells results in almost complete absence of renin-expressing cells in the fetal kidney accompanied by blunted development of the preglomerular arterial tree.…”
Section: Role Of the Camp Pathwaymentioning
confidence: 99%
“…Serial sections (5 m) were deparaffinized in xylenes and graded alcohols. Sections were processed for immunohistochemistry for renin and ␣-smooth muscle actin and stained with hematoxylin or with Masson's trichrome (to assess collagen deposition) as previously described (8,32). To visualize renin granules, 2 m kidney sections were deparaffinized through xylenes and graded alcohols followed by a wash with PBS for 5 min.…”
Section: Generationmentioning
confidence: 99%
“…RNA extraction and cDNA generation by reverse transcription and quantitative real-time PCR using SYBR Green (Invitrogen, Eugene, OR) were performed as previously described (8). Renin mRNA expression was normalized to GAPDH expression.…”
Section: Rna Isolation and Qrt-pcr Analysismentioning
confidence: 99%
“…Using a cultured renin linage cell system, studies observed that its gene expression memory is maintained in the cultured cells and may be re-enacted by cAMP and chromatin remodeling (histone H4 acetylation) (44). Other investigators also noted that CREB-binding protein and p300 (which possess histone acetyltransferase activity) are vital for renin cell distinctiveness, as well as the integrity of the renal architecture (45).…”
Section: Role Of Epigenetics In Ckdmentioning
confidence: 99%